Inhibition of Mitochondrial Biosynthesis Using a "Right‐Side‐Out" Membrane‐Camouflaged Micelle to Facilitate the Therapeutic Effects of Shikonin on Triple‐Negative Breast Cancer. Issue 18 (12th August 2022) - Peng, Jianqing; Hu, Xiaoxia; Fan, Shuangqin; Zhou, Jia; Ren, Shuang; Sun, Runbin; Chen, Yi; Shen, Xiangchun; Chen, Yan
Abstract: The mitochondria represent a potential target for the treatment of triple‐negative breast cancer (TNBC) and shikonin (SK) has shown remarkable therapeutic effects on TNBC. Herein, it is found that SK possesses potent inhibitory effects on mitochondrial biogenesis via targeting polymerase gamma (POLG). However, its application is restricted by its poor aqueous solubility and stability, and therefore, a biomimetic micelle to aid with tumor lesion accumulation and mitochondria‐targeted delivery of SK is designed. A folic acid (FA) conjugated polyethylene glycol derivative (FA‐PEG‐FA) is inserted onto the external membranes of red blood cells (FP‐RBCm) to prepare a "right‐side‐out" RBCm‐camouflaged cationic micelle (ThTM/SK@FP‐RBCm). Both FP‐RBCm coating and a triphenylphosphine (TPP) moiety on the periphery of micelles contribute to tumor lesion distribution, receptor‐mediated cellular uptake, and electrostatic attraction‐dependent mitochondrial targeting, thereby maximizing inhibitory effects on mitochondrial biosynthesis in TNBC cells. Intravenous administration of ThTM/SK@FP‐RBCm leads to profound inhibition of tumor growth and lung metastasis in a TNBC mouse model with no obvious toxicity. This work highlights the mitochondria‐targeted delivery of SK using a "right‐side‐out" membrane‐camouflaged micelle for the inhibition of mitochondrial biogenesis and enhanced therapeutic effects on TNBC. Abstract : A membrane‐camouflaged cationic micelle is designed and prepared for targeted delivery of SK to TNBC cells. ThTM/SK@FP‐RBCm can be effectively taken in by TNBC cells via FR α, escape from lysosome and distribute to mitochondria, which facilitates the inhibitory effects of SK on mitochondrial biogenesis via downregulation of POLG to reduce mtDNA levels, providing a potential therapeutic regimen of TNBC.